Do Competence, Training and Work Environment Impact Teacher Performance (Case Study at MTSS Al Muslim Bireuen Regency) - Mahdi, Mahdi; Yusuf, M.; Afriana, Afriana (peusangan, 2025)
This study analyzes and determines the influence of competency, training and work environment factors on teacher performance, using path analysis. The case study was conducted on 40 teachers at MtsS Al Muslim, Bireuen Regency, with data collection through a questionnaire with a quantitative approach. The results of the study prove that (1) there is a causal relationship between exogenous variables, namely competency, training and work environment with a moderate category. (2) there is a direct and indirect influence of competency on teacher performance of 79.11%. (3) there is a direct and indirect influence of training on teacher performance of 22.17%. (4) there is a direct and indirect influence of the work environment on teacher performance of 20.94%. (5) simultaneously competency, training and work environment affect the performance of MTsS Almuslim Bireuen teachers by 85.6%.